Effect of macroeconomic indicators against ZIS payments in the National Amil Zakat Agency (BAZNAS) 2013-2017 - , Neneng Susilowati (Technium Social Sciences Journal, 2021)
Zakat, donations and alms are one of the instruments in Islam that can overcome poverty. The purpose of this study is to analyze inflation, human development index, per capita income and local revenue against the payment of zakat, infaq and alms at the National Zakat Agency (BAZNAS). This research is quantitative in nature and uses secondary data. Secondary data were obtained from the Central Bureau of Statistics, BAZNAS, and Bank Indonesia from 2013-2017 and covers 28 provinces in Indonesia. The type of data used is a combination of time series and cross section data. The results of this study indicate that inflation and the human development index have a negative and insignificant effect on the payment of zakat, infaq and alms. Income per capita has a positive and significant effect on zakat payments, Infaq and alms. Original Regional Income has a positive and insignificant effect on the payment of zakat, infaq and alms.